Using the Picture Word Inductive Model, Art and ACTFL 5 C’s to learn a second or foreign language - Sanchez, Ana Cristina; Arias-Zelidon, Maria Elena (Advances in Social Sciences Research Journal, 2020)
This paper will examine how art can be used as a visual aid and a primary input to teach and learn the Spanish language and culture. Art will be limited to the use of photographs and paintings that will be combined with the Picture Word Inductive Model [PWIM] and the 5C goal areas on the teaching of a foreign language as recommended by the American Council on the Teaching of Foreign Languages [ACTFL]. The five C goals stand for Communications, Culture, Connections, Comparisons, and Communities. The Picture Word Inductive Model [PWIM] was developed by the Language Arts Specialist, Emily Calhoun in 1998 to help children expand their vocabulary repertoire and develop reading and writing skills using pictures. Art is a meaningful input that promotes vocabulary acquisition, listening, speaking, and literacy skills. It can be incorporated into any curriculum regardless of the language methodology to build background knowledge, scaffolding as a bridge from existing knowledge and new information. Art also promotes motivation on the students ‘part, which is a key aspect to successful learning. The researchers will provide a unit plan that can be incorporated in a fourth or fifth-semester Spanish course.